« L’intimité, moi je la fais. » L’intimité masculine incarcérée : entre intrusions contraignantes et tactiques négociées - Anaïs Tschanz (Genre, Sexualité et Société)
In a carceral environment characterized by permanent community life, privacy is an important and complex issue. It is often overlooked, however, particularly when it relates to male prisoners, whose need for privacy seems to conflict with the performativity of gender expected in an environment where hypermasculinity reigns. By referring to the concept of “tactics”, this paper aims to understand the agentic practices male prisoners deploy to (re)build meaningful privacy, through the daily negotiation of their carceral space and the items which compose it. Drawing from semi-directive interviews conducted with male prisoners in Quebec, this paper unveils the dialectic at the center of which prisoners attempt to preserve their privacy, between intrusions of various origins (institutional and personal) and multifaceted tactics (individual and collective).